2016
DOI: 10.18632/oncotarget.12167
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anti-EGFR immune response with mimotopes identified from a phage display peptide library by panitumumab

Abstract: The epidermal growth factor receptor (EGFR) is overexpressed in several epithelial tumors. Anti-EGFR humanized monoclonal antibodies, cetuximab and panitumumab, in combination with chemotherapy have improved the prognosis for patients with wild-type RAS tumors. To identify mimotopes of EGFR and develop mimotope-based EGFR vaccines, we screened a phage display peptide library with panitumumab. Two EGFR mimotopes P19 and P26, which could be recognized by panitumumab specifically, were isolated. To enhance the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The MTT assay was performed to determine the cell proliferation and cell sensitivity to rapamycin as previously described 26 , 27 . Briefly, cells (0.5×10 4 cells/well) transfected with plasmids or siRNAs were seeded in 96-well plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTT assay was performed to determine the cell proliferation and cell sensitivity to rapamycin as previously described 26 , 27 . Briefly, cells (0.5×10 4 cells/well) transfected with plasmids or siRNAs were seeded in 96-well plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant His-CENPH and GST-GOLPH3 protein were expressed and purified according to manufacturer's instructions (Amersham). GST pull-down and His-tag pull-down assays were performed as described previously 27 , 28 . Briefly, E. coli cell lysates containing GST and His-tag fusion protein were prepared in lysis buffer (1% Triton X-100, 1 mmol/L PMSF, and 1 mg/mL lysozyme in PBS) followed by sonication.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant fusion protein of P19/P26/heat shock-related protein (HSP) 70, used for immunization, induced the production of specific antibodies against the peptides and EGFR. This allowed consideration of these peptides as mimotopes suitable for vaccines for anti-EGFR immunotherapy in tumors [ 113 ]. HER2 is a 185-kDa transmembrane glycoprotein with an extracellular domain of 105 kDa (p105HER2 ECD).…”
Section: The Epidermal Growth Factor Receptor Familymentioning
confidence: 99%
“…In situ phage display studies include what was reported by Li et al over a decade ago and allowed the discovery of the GE11 peptide (YHWYGYTPQNVI) [ 39 ], still largely used to target EGFR [ 118 , 119 , 120 ]. The EGFR mimotopes, P26 (VPGWSQAFMALA) and P19 (DTDWVRMRDSAR), were also recently identified [ 121 ]. Other examples include the LS-7 (LQNAPRS) peptide which targets the CSC-associated marker CD133 [ 122 ] and the new nanobody VUN100 for targeting the G-protein coupled receptor homolog US28 that is found to be overexpressed in glioblastoma [ 123 ].…”
Section: Targeting Approaches In the Context Of Cancermentioning
confidence: 99%